Workload Measurement Models In Hospital: Literature Review - Yeni Susilawati; Maria Komariah; Irman Somantri (Journal Research of Social Science, Economics, and Management, 2023)
Nurse workload is all activities, activities, actions taken by a nurse while the nurse is on duty in a hospital service unit. The purpose of this literature is to identify which method is more effective and efficient to measure the workload of nurses. Article review was carried out through several electronic databases including Google Scholar, Google Scholar, Pubmed with the keyword "nurse workload", inclusion criteria included articles published between 2015 and 2022, full text in both English and Indonesian. A literature search found 72 articles, then 51 articles were removed according to the exclusion criteria, so that only 8 articles were identified. The results of the literature study show that the WISN method is most often used to determine the workload of health workers, not only nurses. made by several people including Richa Noprianty et al, 2020 with the topic Analysis of Nurses Staff Needs Using Workload Indicate Staff Need in Pediatric Ward with Time Motion Study, Taufique Joarder et al, 2020 with the topic Assessment of staffing needs for physicians and nurses at Upazila health complexes in Bangladesh using WHO workload indicators of staffing need (WISN) method and Angélica Araújo de Menezes et al,  2022 with the topic Application of the workload indicators of staffing need method to calculate the size of the medical staff at a maternity hospital in the state of Bahia, Brazil. But beyond that, it doesn't mean that other methods are ineffective, because each method has its own advantages and disadvantages, it's up to the researchers or the hospital to choose which method to use.